Implementasi Akuntansi Sumber Daya Manusia Pada PT. Perkebunan Nusantara III (Persero) Medan - Rizky Ananda Dafitra Siregar; Nurlaila Nurlaila (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Human resource accounting is considered strategic because employees are not only considered as operational costs, but also as assets that make a real contribution to the company's success. This means that human resource management does not only revolve around recording employee-related expenses, but also involves measuring the added value provided by the workforce towards achieving company goals. This research uses a descriptive qualitative research method, in the research